Adaptive level set method for accurate boundary shape in optimization of electromagnetic systems. Issue 3 (29th April 2014) - Hyouk Lee, Kang; Geon Hong, Seung; Ki Baek, Myung; Soon Choi, Hong; Sun Kim, Young; Han Park, Il
Abstract : Purpose: – The purpose of this paper is to present a new numerical technique, called adaptive level set method, for use with the finite element method. Design/methodology/approach: – A conventional level set method using the smeared Heaviside function has been employed for shape and topology optimizations. The smeared Heaviside function yields an indistinct interface boundary, and so can increase computational time and cause numerical errors. The adaptive level set method does not use the smeared Heaviside function. To coincide with the material interface, it processes the zero level as the boundary data of element meshing. Findings: – Usefulness and accuracy of shape optimization using the adaptive level set method are shown by comparison to the conventional level set method. A shape optimization procedure using the adaptive level set method is introduced. Numerical examples are employed to explain how the adaptive level set method is applied. Originality/value: – The adaptive level set method is proposed to relieve the interface problem of the conventional level set method. Shape variation in the optimization is calculated from the continuum sensitivity analysis.